Penerapan Model Project Based Learning (PjBL) dalam Meningkatkan Keterampilan Menulis pada Pembelajaran Bahasa Indonesia - Restika Wijayanti (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research is entitled Application of Project Based Learning (PjBL) Model in Improving Writing Skills in Indonesian Language Learning with a focus on the application of project-based learning methods in improving students' writing skills. The Project Based Learning (PjBL) model is a learning approach that emphasizes the active involvement of students through real projects that are relevant to everyday life. This study aims to explore the effectiveness of the application of PjBL in improving students' writing skills in Indonesian language learning. The research method used is qualitative with a literature review approach, analyzing ten scientific articles published in the period 2022 to 2024. The results showed that the implementation of PjBL significantly improved students' writing skills, as well as encouraged the development of creativity, collaboration, and critical thinking skills. In addition, students reported increased motivation and engagement in the learning process. Nonetheless, challenges in implementing PjBL, such as the need for thorough preparation from teachers and effective time management, need to be considered. The conclusion of this study confirms that PjBL is an effective method to improve students' writing skills, and can be integrated in Indonesian language learning to create a more interesting and meaningful learning experience. The results of this research emphasize that PjBL is an effective, innovative and relevant learning method for equipping students with 21st century skills.